Edukasi Hipertensi dan Intervensi Pemberian Jus Tomat dan Timun bagi Lansia - Evi Suryaningsih; Sindi Silvia; Dayang Pertiwi; Della Yunita Nadeak; Murniati Murniati (Jurnal Pengabdian Mitra Persada, 2026)
Hypertension is a major public health concern contributing significantly to morbidity and mortality, particularly among the elderly population. Educational activities and the administration of tomato and cucumber juice serve as potential non-pharmacological interventions to support blood pressure reduction. This study aims to analyze the implementation of hypertension counseling and the tomato–cucumber juice intervention among elderly residents in Sumber Sari Village. The method employed included educational sessions through lectures, discussions, and blood pressure measurements before and after the intervention. The results demonstrated a decrease in both systolic and diastolic blood pressure among most participants after consuming the juice. Additionally, the activity improved participants' understanding of hypertension and its prevention. It is concluded that health education combined with simple nutritional interventions such as tomato and cucumber juice is effective as a promotive and preventive approach to hypertension.